Simultaneous Management of Retinal Detachment and Aphakia with Pars Plana Vitrectomy, Silicone Oil Tamponade and Retropupillary Iris-Claw Intraocular Lens Implantation in Patients with Marfan Syndrome - Hsin, Safia; Stappler, Theodor; Potic, Jelena; Wolfensberger, Thomas J.; Konstantinidis, Lazaros (Klinische Monatsblätter für Augenheilkunde, 2022)
Background Marfan Syndrome is an autosomal dominant disease with multiple ocular abnormalities including ectopia lentis and a high incidence of rhegmatogenous retinal detachment (RRD). The management of RRD may be challenging in cases of aphakic patients with Marfan.Purpose To report on the management of four cases of simultaneous RRD and aphakia with vitrectomy, silicone oil tamponade, and retropupillary iris-claw intraocular lens (IOL) implantation in patients with Marfan that have been operated at the Jules-Gonin Eye Hospital between 2019 and 2020.History and Signs Ages at presentation were 20, 30, 32, and 31 years, respectively. All patients had a history of extraction of a dislocated lens. None of the patients had a previous posterior vitrectomy. Two patients had records of previous measurements for IOL calculation by optical biometry (IOL Master, Carl Zeiss Meditec AG, Jena, Germany) about 1 year prior to the RRD development. In two cases, measurements for IOL calculation by optical biometry were based on the contralateral eye.Therapy and Outcome All patients underwent 23 G vitrectomy, peripheral iridotomy, and retropupillary iris-claw IOL. No intraoperative complications were encountered. All patients had silicone oil tamponade, one of which required heavy silicone oil. Silicone oil was removed 3 months following primary surgery. Minimum follow-up was 1 year. The single surgery anatomic success rate was 100%. All patients had visual acuity of at least 0.8 at the last follow-up (1.25, 1.0, 0.8, and 0.8 respectively). The targeted refractive results were accurately achieved in all four cases postoperatively. One patient presented ocular hypertension 2 weeks after surgery due to presumed steroid response and was managed conservatively. None of the patients had silicone oil migration into the anterior chamber.Conclusion Retropupillary iris-claw IOL implantation in cases of RRD and aphakia creates a barrier to tamponades from the posterior segment, effectively preventing them from entering the anterior segment of the eye. Therefore, the management of aphakia and retinal detachment with simultaneous vitrectomy and a retropupillary iris-claw IOL may be a successful strategy in reducing postoperative complications in patients with Marfan syndrome.
Keywords: aphakia; rhegmatogenous retinal detachment; Marfan syndrome; pars plana vitrectomy